The formative evaluation of an assessment framework to identify psychosocial issues experienced by the families of children who are seriously or chronically ill - Tallon, Mary; Kendall, Garth; Priddis, Lynn (2015)
Aim: The views of parents and health care professionals’ about discussing family issues when a child is in hospital are presented. Data were gathered in a major children’s hospital to finalise a family psychosocial assessment framework that is acceptable and ready for implementation. Background: Family-centred care (FCC) is accepted as the way to care for children in hospital. In practice, this often means that a parent simply ‘rooms in’ with their child. Yet, FCC is a process of engagement, information sharing and support giving so that the child’s primary care-giver feels competent to give appropriate care in the short and long-term. While many nurses do provide this type care, many do not. There is no framework in place to guide nurses to objectively assess family functioning and plan care to optimise the child’s health and developmental outcomes. Parents often require considerable support as the associated distress frequently affects parental capacity to provide appropriate care, particularly when their child is vulnerable to emotional and behavioural problems. Research Plan: A formative evaluation was undertaken using a best-practice model that includes a group of factors found to be predictive of poor child health and developmental outcomes. Validated instruments measuring attitudes towards psychosocial assessment were administered and participants were asked to discuss their perceptions. Results: Both parents and health professionals stated that they believed it is important for staff to ask parents about maternal wellbeing, life-stress, family functioning and support, while asking about parental education and occupation is not. Health professionals with more experience were more positive about psychosocial assessment. Parents living in less advantaged areas were less positive about discussing psychosocial issues. Discussion: There is a need for implementation of a family psychosocial assessment framework in the paediatric setting. The framework should focus on psychosocial issues related to care-giving rather than socioeconomic characteristics.